Survei Kepuasan Pemustaka di Perpustakaan Pascasarjana UIN FAS Bengkulu untuk Peningkatan Mutu Layanan - Sutriono Sutriono; Jurianto Jurianto (Maktabatuna, 2025)
This research is a field research using quantitative descriptive, data obtained from the results of observations, literature studies and questionnaire distribution. The subjects of the study were 40 librarians who had visited the library. Samples were taken as many as 40 respondents consisting of students of various study programs in the Postgraduate Program of UIN Fatmawati Sukarno Bengkulu. The results of this study in general the level of satisfaction of librarians from 40 respondents who gave answers 23 people were very satisfied both in terms of services, facilities and infrastructure as well as collections and responsiveness of librarians where the average number of librarian satisfaction reached 45-55%, while those who stated that they were quite satisfied were only 7-12% or as many as 3-5 people only, however, postgraduate librarians still provided input and suggestions including the following: a). Related to the collection, the need to add subscriptions to international journals, reference books, Addition of books on biographies of Ulama and figures of the archipelago and the world. b). Regarding facilities and infrastructure, the Postgraduate librarians proposed the provision of toilets on the 2nd floor, expansion of the reading room and the addition of reading table facilities, improvement of air conditioning (AC) facilities and utilization of information technology in services. c). Regarding human resources, it is very necessary to add and improve the quality of librarian resources through continuous competency improvement.